TESTIMONIUM DE AUDITU TELAAH PERSPEKTIF HUKUM ACARA PERDATA DAN FIQH - Asmuni Asmuni (Jurnal Hukum dan Peradilan, 2014)
The witness is the person or party who hear and know themselves what the testimony. However, there are also witnesses called testimonium de auditu namely hearing the testimony of others, meaning that the information obtained from another person or not known directly. This testimony is called the Shahadah according fiqh al Istifāḍah and some are calling it the bi al-Shahada al-Tasâmu'i. Theoretically, testimonium de auditu be a problem as opposed to the actual meaning of the witness. Therefore in practice, especially among the jurists' disagreement occurs. Departing from this disagreement, the problems discussed in the testimony of the strength of the testimony of two perspectives: in civil law and jurisprudence. From this exploratory study found that testimonium de auditu can not be used as direct evidence in the trial, but a testimony de auditu can be constructed by a judge as an allegation by a judge. While Shahada al Istifāḍah in Islamic civil law has the power and strength are perfect even on specific issues such as ownership and determination of offspring. Even the jurists' further states that the strength of this testimonium stronger testimony of two witnesses who qualify formal and material requirements. Keywords: Testimonium de Auditu, Procedural Law, Fiqh